Antibacterial Activity of Quaternary Ammonium Salt from Diethylaminoethyl Methacrylate - Makhloufia Mohammed; BenaÏssa Tahar; Derdour AÏcha; Henni Djamel Eddine (E-Journal of Chemistry)
A quaternary ammonium salt was synthesized from diethylaminoethyl methacrylate (DEAEMA) by quaternization with hexadecyl bromide. The resultant compound (Am-h) was characterized by FTIR and NMR spectroscopy. Its bactericidal activity was evaluated by determining minimum inhibitory concentration (MIC) values and inhibitory zone diameter against gram positive bacteria (Streptococcus sp.) and gram negative bacteria such as Acenito baumannii, Klebsiella pneumoniae and Proteus sp. respectively. The results showed that the MIC values of the synthesised compound (Am-h) were 2 μg/mL against Acenito baumannii, Klebsiella pneumoniae, Proteus sp. and Streptococcus sp.